PENGARUH SKEPTISME PROFESIONAL DAN EMOTIONAL SPIRITUAL QUOTIENT AUDITOR TERHADAP KUALITAS AUDIT - Salsabila Khairani (2023)
This research is a quantitative study that aims to find out how professional skepticism and emotional spiritual quotient auditors affect audit quality. Auditors who work at BPK RI, AKN I - AKN VII work units are used as samples. Purposive sampling technique is a technique used to select samples with certain criteria. The software used for hypothesis testing is SmartPLS 3.2.9 with SEM analysis and a significance value of 5% (0.05). Based on the test results, it is found that professional skepticism has a significant effect on audit quality, while the emotional spiritual quotient does not have a significant effect on audit quality.